Karadenizia, a new monospecific pachyiuline genus (Diplopoda: Julida: Julidae) from Turkey - Antić, Dragan (Zootaxa, 2023)
The present paper is dedicated to the description of the monospecific pachyiuline genus Karadenizia gen. nov. with the type species K. merti sp. nov. from Erçek Cave near the southern coast of the Black Sea in Turkey. In addition to the diagnosis and detailed description, brief notes on the locality and known ecology of this taxon are given. The relationship of this genus with some other pachyiulines is discussed based on the structure of the gonopods and some somatic features. The interesting colouration of the new taxon allows a brief discussion and hypothesis on the possible defensive role of such a colour pattern, which is also known in some other millipedes.